Indirect predictive control strategy with fixed switching frequency for a direct matrix converter - Rivera, Marco; Tariscotti, Luca; Wheeler, Patrick; Bayhan, S. (2017)
The direct matrix converter has a large number of available switching states which implies that the implementation of predictive control techniques in this converter requires high computational cost while an adequate selection of weighting factors in order to control both input and output sides. In this paper, an indirect model predictive current control strategy is proposed in order to simplify the computational cost while avoiding the use of weighting factors. The method is based on the fictitious dc-link concept, which has been used in the past for the classical modulation and control techniques of the direct matrix converter. The proposal is enhanced with a fixed switching predictive strategy in order to improve the performance of the full system. Simulated results confirm the feasibility of the proposal demonstrating that it is an alternative to classical predictive control strategies for the direct matrix converter.